Perceived Teacher Responses to Bullying Influence Students’ Social Cognitions - Demol, Karlien; Verschueren, Karine; Salmivalli, Christina; Colpin, Hilde (Frontiers in Psychology, 2020)
Teachers’ responses to bullying incidents are key in bullying intervention at school. Scholars have suggested that teacher responses can predict student cognitions that are associated with their bullying behaviors. However, little is known about whether and how teacher responses affect these cognitions. Therefore, the current study investigated the effects of four immediate teacher responses on four bullying-related student cognitions, using an experimental vignette design. Additionally, it was examined whether students’ own participant role behaviors in actual bullying moderated these effects. The investigated teacher responses were non‐response, comforting the victim, correcting the bully, and a combination of comforting the victim and correcting the bully. The investigated student cognitions were perceived teacher attitudes towards bullying, perceived teacher moral disengagement regarding bullying, student willingness to report bullying to the teacher and student expectations regarding bullying participant role behaviors in the classroom. Fourth-to-sixth grade students (N=910; 47% boys; Mage = 11.04 years, SD = .91) read a vignette describing a hypothetical teacher’s response to a same bullying incident, following random assignment to one of eight conditions (i.e., four teacher responses x two genders of bully and victim in the vignette). Afterwards, students completed questionnaires about their social cognitions and manipulation checks. Analyses of variance demonstrated that students perceived stronger teacher anti-bullying attitudes and less teacher moral disengagement when the hypothetical teacher displayed an active response. These effects were even stronger when the teacher corrected the bully compared to when only the victim was comforted. Further, students were more willing to report bullying when the teacher corrected the bully than when the teacher only comforted the victim. Finally, students expected less pro-bullying behaviors, more defending and less victimization in the vignette’s classroom following active teacher response compared to non-response. The effects of teacher responses on student cognitions were not moderated by students’ own participant roles in bullying. Taken together, these findings emphasize the importance of active teacher responses to bullying, and especially, responses that clearly show that bullying is not tolerated. Teachers are encouraged to be aware that students can deduce beliefs from teacher responses which can, in turn, affect bullying processes in the classroom.